Pertumbuhan Ikan Hiu Tupai (Chiloscylium hasselti) di Perairan Tanjung Balai, Provinsi Sumatera Utara, Indonesia - Wini A. J. Harahap; Amanatul Fadhilah (AQUACOASTMARINE, 2018)
This scientific report aim to analyze the growth patterns of Tupai shark (Chiloscylium hasselti) at Tanjungbalai Waters in Province of North Sumatera, Indonesia. This scientific report take survey methode during two months start from march until upril 2018. The result showed that the b value of Tupai shark is 0,269 or allometric negative with condition factor are among 0,0021 until 0,0140.Keywords: Chiloscylium hasselti, Allometric negative, Tanjungbalai.